The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.3892/ijmm.2013.1481
|View full text |Cite
|
Sign up to set email alerts
|

Duhuo Jisheng Decoction promotes chondrocyte proliferation through accelerated G1/S transition in osteoarthritis

Abstract: Abstract. Duhuo Jisheng Decoction (DHJSD), a well known traditional Chinese folk medicine, is used for eliminating stagnation, removing blood stasis, promoting blood circulation and alleviating pain; it is commonly used for the treatment of various diseases, including osteoarthritis (OA). However, the molecular mechanisms behind the therapeutic effects of OA remain unclear. In the present study, the effects of DHJSD on the morphology of articular cartilage and the G1/S cell cycle progression in chondrocytes, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…It has been widely used for treating OA (21), and a previous study indicated that DHJSD contains drug-and lead-like compounds with potential synergy and polypharmacology against OA (22). An in vivo study demonstrated that treatment with DHJSD promotes the progression of chondrocytes from G 1 to S phase (23), and this may be one of the mechanisms underlying its use in OA. In addition, previous studies have reported that chondrocytes treated with IL-1β produce a particularly effective cell model of the mechanisms involved in degenerative arthropathies (24).…”
Section: Duhuo Jisheng Decoction-containing Serum Promotes Proliferatmentioning
confidence: 97%
“…It has been widely used for treating OA (21), and a previous study indicated that DHJSD contains drug-and lead-like compounds with potential synergy and polypharmacology against OA (22). An in vivo study demonstrated that treatment with DHJSD promotes the progression of chondrocytes from G 1 to S phase (23), and this may be one of the mechanisms underlying its use in OA. In addition, previous studies have reported that chondrocytes treated with IL-1β produce a particularly effective cell model of the mechanisms involved in degenerative arthropathies (24).…”
Section: Duhuo Jisheng Decoction-containing Serum Promotes Proliferatmentioning
confidence: 97%
“…As shown in Figure 7, DHJSD has an overall effect to eliminate "fenghan-shi", respectively, and thus to relieve pain of "Bi Zheng" through promoting "Gan" and "Shen" function and therefore strengthen the bones and tendons [30] . It also improves circulation and remove stasis of "Qi" and "Xue", reduces tissue swelling and relieves pain [20,22,23,26,32,39,40] . Some pharmacological studies have demonstrated that DHJSD may have effects of analgesia, immune function regulation, blood vessel dilation, anti-inflammation, and antiplatelet aggregation [20,22,23,26,32,39,40] .…”
Section: Discussionmentioning
confidence: 99%
“…It also improves circulation and remove stasis of "Qi" and "Xue", reduces tissue swelling and relieves pain [20,22,23,26,32,39,40] . Some pharmacological studies have demonstrated that DHJSD may have effects of analgesia, immune function regulation, blood vessel dilation, anti-inflammation, and antiplatelet aggregation [20,22,23,26,32,39,40] . In a study of the aging-related osteoarthritis, another common bone degenerative disease, Chen et al found that DHJSD may inhibit VEGF and HIF-1α to retard cartilage degradation in a rabbit model of osteoarthritis [53] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations